Use and application of gelatin as potential biodegradable packaging materials for food products - Zainal Abedin, Nur Hanani; Roos, Yrjo H.; Kerry, Joe P. (Elsevier BV, 2014)
The manufacture and potential application of biodegradable films for food application has gained increased interest as alternatives to conventional food packaging polymers due to the sustainable nature associated with their availability, broad and abundant source range, compostability, environmentally-friendly image, compatibility with foodstuffs and food application, etc. Gelatin is one such material and is a unique and popularly used hydrocolloid by the food industry today due to its inherent characteristics, thereby potentially offering a wide range of further and unique industrial applications. Gelatin from different sources have different physical and chemical properties as they contain different amino acid contents which are responsible for the varying characteristics observed upon utilization in food systems and when being utilized more specifically, in the manufacture of films. Packaging films can be successfully produced from all gelatin sources and the behaviour and characteristics of gelatin-based films can be altered through the incorporation of other food ingredients to produce composite films possessing enhanced physical and mechanical properties. This review will present the current situation with respect to gelatin usage as a packaging source material and the challenges that remain in order to move the manufacture of gelatin-based films nearer to commercial reality.